2005
DOI: 10.1385/jmn:25:1:105
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia-Associated Forms of TorsinA Are Deficient in ATPase Activity

Abstract: Early-onset dystonia is caused by mutations in the torsinA protein, a putative member of the AAA+ class of ATPases. In this study we have evaluated the ATPase activity of bacterially expressed wild-type torsinA and its disease-associated mutant forms. Upon overexpression in Escherichia coli, recombinant torsinA proteins were accumulated as insoluble inclusion bodies and required refolding to become soluble and catalytically active. The refolded wild-type and mutant torsinA proteins were capable of hydrolyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Secondly, as Zhu and others have pointed out, previous studies that have investigated the ATPase activity of WT torsinA and torsinA (ΔE) have been contradictory and did not have an ATP hydrolysis mutant as a negative control. These studies have also shown much lower rates of activity than that of other AAA+ proteins as well as conflicting results between the ATPase activity of WT torsinA and torsinA (ΔE) (Kustedjo et al 2000;Konakova and Pulst 2005;Pham et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, as Zhu and others have pointed out, previous studies that have investigated the ATPase activity of WT torsinA and torsinA (ΔE) have been contradictory and did not have an ATP hydrolysis mutant as a negative control. These studies have also shown much lower rates of activity than that of other AAA+ proteins as well as conflicting results between the ATPase activity of WT torsinA and torsinA (ΔE) (Kustedjo et al 2000;Konakova and Pulst 2005;Pham et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Published data of purified human torsinA showed that ⌬20aa torsinA hydrolyzed ATP with a V max of 0.11 Ϯ 0.01 nmol min Ϫ1 g Ϫ1 and K m of 1.1 Ϯ 0.2 mM (Kustedjo et al, 2003); Maltose-binding protein (MBP)-torsinA with a 52-amino acid N-terminus deletion has a reported specific activity of 20 pmol min Ϫ1 g Ϫ1 (Pham et al, 2006), both of which were detected by [␣-32 P]ATP and polyethyleneiminecellulose thin-layer chromatography. His-NusA-His-S-tagged torsinA purified from E. coli inclusion bodies catalyzed ATP with a V max of 70 nmol P i min Ϫ1 mg Ϫ1 and K m of 15 M using P i assay (Konakova and Pulst, 2005). Noticeably, these three reports are not consistent with each other and no negative control, such as the E171Q mutant in which the catalytic glutamate is mutated to glutamine, was tested to confirm ATP hydrolysis.…”
Section: Oligomerization and Atpase Activity Of Torsin Family Proteinsmentioning
confidence: 99%
“…1A). Deletion of Glu-302/Glu-303 causes a variety of alterations in torsinA's properties, including protein stability, degradation, subcellular localization, conformational change, and molecular interactions (57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). How these alterations lead to EOTD is undetermined, which precludes the rational design of targeted therapies to control EOTD progression or prevent the disease.…”
mentioning
confidence: 99%